MEDIA POP UP BOOK GARUDA INDONESIA UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS III SEKOLAH DASAR - Wijayanto, Sugeng Pangestu; Pratiwi, Ika Ari; Kironoratri, Lintang (Universitas Muria Kudus, 2024)
The aim of this research is to improve speaking skills using the Garuda Indonesia pop up book media for class III students at SD Negeri 02 Ngembal Kulon. Pop up book media is media with 3D elements when the page is opened. The problem that researchers found in their research was that there were still students' speaking skills that were relatively low.The research method used is Classroom Action Research (CAR) with the Kemmis Mc model. Taggart. The research was carried out through two cycles, and each cycle consisted of two meetings. The subjects in this research were class III students at SD Negeri 02 Ngembal Kulon, totaling 10 students. Data collection techniques used include observation, interviews, tests and documentation.The results of the research showed that there was an increase in speaking skills using the Garuda Indonesia pop up book media for class III students at SD Negeri 02 Ngembal Kulon. The results of the students' speaking skills obtained an average percentage score of 70% in cycle I, then continued in cycle II, increasing by 10% to 80% in the skilled category.Based on the results of Classroom Action Research or CAR which was carried out in class III of SD Negeri 02 Ngembal Kulon, it can be concluded that the application of Garuda Indonesia's pop up book media can improve students' speaking skills.